2007
DOI: 10.1021/ja070235b
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Mechanism of the Negishi Reaction:  ZnRX versus ZnR2Reagents

Abstract: The observation that their transmetalations with trans-[PdRfCl(PPh3)2] (Rf = fluoroaryl) give stereoselectively a different isomer of [PdRfMe(PPh3)2] suggests that Negishi reactions with ZnRX or ZnR2 could show very different evolutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(65 citation statements)
references
References 8 publications
1
64
0
Order By: Relevance
“…[46] Recently, Sanford and co-workers studied, computational and experimentally, the influence of ancillary ligands on the ligand disproportionation of cis- L 2 ] intermediates, which eventually leads to undesired homocoupling products in the cross-coupling reactions (Scheme 21). [48][49][50] Lo Sterzo et al have reported a number of examples of palladium-catalyzed metal-carbon bond-formation with alkynyl stannanes (Scheme 22), [51][52][53][54] and have detected spectroscopically a pentacoordinated palladium intermediate that is suggested to be a model of the transition state proposed in the cyclic mechanism of the Stille reaction.…”
Section: Introductionmentioning
confidence: 99%
“…[46] Recently, Sanford and co-workers studied, computational and experimentally, the influence of ancillary ligands on the ligand disproportionation of cis- L 2 ] intermediates, which eventually leads to undesired homocoupling products in the cross-coupling reactions (Scheme 21). [48][49][50] Lo Sterzo et al have reported a number of examples of palladium-catalyzed metal-carbon bond-formation with alkynyl stannanes (Scheme 22), [51][52][53][54] and have detected spectroscopically a pentacoordinated palladium intermediate that is suggested to be a model of the transition state proposed in the cyclic mechanism of the Stille reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Keywords: cross-coupling · density functional calculations · N-heterocyclic carbenes · palladium · zinc steps: 1) oxidative addition (OA): insertion of Pd 0 into the carbon-halide bond with Pd 0 being oxidized to Pd II ; 2) transmetalation (TM): transfer of the second carbon fragment to Pd II from an organometallic compound concomitant with inorganic salt formation, which dissociates from the complex; 3) reductive elimination (RE): expulsion of the product hydrocarbon with regeneration of the Pd 0 catalyst. The importance of Pd-mediated cross-coupling has led to numerous computational studies that have revealed important insights into the structure and behavior of NHC-Pd [7][8][9] and phosphane-Pd [10,11] catalysts and actual or putative catalytic cycle intermediates as well as the nature of oxidative addition, [11][12][13] transmetalation, [14] and reductive elimination [15] steps. Computational analysis of whole catalytic cycles [9,16] have been performed much less frequently.…”
mentioning
confidence: 99%
“…Notably, both aryl groups are transferred from their organozinc reagents to the organic halide. [16] The highest rates of conversion and yields were observed when the reactions were performed in NMP/ THF ( % 4:1) mixtures (NMP = N-methylpyrrolidone). [17] When diphenylzinc was allowed to react, for example, with various, non-ortho-substituted aryl bromides and aryl chlorides with either electron-withdrawing or electron-donating groups, such as 1-(4-chlorophenyl)ethanone, 1-(3-chlorophenyl)ethanone, (4-bromophenyl)A C H T U N G T R E N N U N G (phenyl)methanone, ethyl 4-bromobenzoate, and 5-bromo-2-benzofuran-1A C H T U N G T R E N N U N G (3 H)-one, as well as with 1-chloro-4-methylbenzene, 1-bromo-4-ethenylbenzene, or imines such as N-[(1E)-(4-bromophenyl)methyliden]aniline, or with 1-bromo-3-(diethoxymethyl)benzene, 1-bromo-4-methoxybenzene, or 1-bromo-3,5-dimethoxybenzene in the presence of the catalyst (0.1 mol %), the corresponding biaryls were cleanly formed in yields of > 80 % in only 30 min when aryl bromides are used and within 1 h when aryl chlorides were applied (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…[16] Reductive elimination of the cross-coupling product (aryl-aryl') closes the catalytic cycle and regenerates the catalyst (cycle A).…”
Section: A C H T U N G T R E N N U N G Iden]aniline)mentioning
confidence: 99%